2020
DOI: 10.3167/asp.2020.140113
|View full text |Cite
|
Sign up to set email alerts
|

Book Reviews

Abstract: Cristina A. Bejan, Intellectuals and Fascism in Interwar Romania: The Criterion Association, Cham, Switzer land: Palgrave, 2019, 323 pp., €74.89 (hardback), ISBN 978-3-030-20164-7.Chiara Bonfiglioli, Women and Industry in the Balkans: The Rise and Fall of the Yugoslav Textile Sector, London: I. B. Tauris, 2020, 232 pp., £85 (hardback), ISBN: 978-1-78533-598-3.Aslı Davaz, Eşitsiz kız kardeşlik, uluslararası ve Ortadoğu kadın hareketleri, 1935 Kongresi ve Türk Kadın Birliği (Unequal sisterhood, international an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…14 The memoirs fi rst saw print in English in 2019; I had written on them elsewhere. 15 However, I found that their structure justifi es their inclusion here. The fi rst part of the book refl ects on the interwar period and is preceded by an introduction by the author's son, historian Hubert Zawadzki, who not only talked his mother into writing the work but also prepared it for publication.…”
Section: Autobiographical Writing and Gendermentioning
confidence: 80%
“…14 The memoirs fi rst saw print in English in 2019; I had written on them elsewhere. 15 However, I found that their structure justifi es their inclusion here. The fi rst part of the book refl ects on the interwar period and is preceded by an introduction by the author's son, historian Hubert Zawadzki, who not only talked his mother into writing the work but also prepared it for publication.…”
Section: Autobiographical Writing and Gendermentioning
confidence: 80%